THE STUDY OF PRACTICAL WAYS OF AESTHETIC EDUCATION OF FOREIGN STUDENTS IN CHINESE UNIVERSITIES IN THE CONTEXT OF THE “BELT AND ROAD” INITIATIVE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Aesthetic education of foreign students in Chinese universities is an effective way to train highly qualified international personnel who promote civilized exchange and mutual understanding, as well as those with language skills, certain knowledge about China, intercultural and global competence, who love and understand China. However, in the process of aesthetic education of foreign students in Chinese universities, there are real difficulties, such as cultural and linguistic differences between China and other countries, difficulties in interpersonal communication and inconsistencies in educational and management models that require their own coverage and solutions. An in-depth analysis of the value content of aesthetic education of foreign students shows that it can help foreign students quickly integrate into Chinese culture, adapt to the social environment and improve their Chinese language skills. This allows them to understand China more deeply, familiarize themselves with Chinese culture and develop a love for China. Therefore, practical ways of aesthetic education of foreign students in Chinese universities are proposed through the optimization of aesthetic education courses, strengthening the staff of teachers, creating platforms for exchange and practice in the field, promoting academic exchange in this field and creating a digital intellectual platform. These measures will help international students better understand and immerse themselves in the unique traditional culture of China.
Keywords: international students in China, aesthetic education, “Belt and Road” initiative, the community of the common destiny of mankind, practical ways